Química mineral de anfibólios e biotitas do granito paleoproterozóico São João, Província Carajás, Pará - MELO, Leandro Jorge Tavares (2018)
The São João Granite (SJG) is an anorogenic batholith that intrudes Archean units of the Rio Maria Domain, southeastern Amazonian Craton. Among the four petrographic facies, two of them were analyzed in scanning electron microscopy: biotite-amphibole monzogranite (BAMG) and biotite-amphibole syenogranite (BASG). In both facies the amphiboles are Fe-hornblende in composition and shows low Mg/(Mg+Fe) ratios which varies from 0,04 to 0,26. The biotite in both facies is ferroan with high Fe/(Fe+Mg) ratios (> 0,8) and approaches annite in composition. The Al-in hornblende geobarometer indicated intermediate pressures of emplacement to the SJG which varies from 3 to 5 kbar. However, is possible that the calculated pressures are overestimated because the amphiboles have Fe/(Fe+Mg) ratios higher than 0,75. The zircon geothermometer suggest initial crystallization temperatures between 850°C and 883°C, whereas the near solidus temperatures indicated by the amphibole geothermometer are of 716°C to 776°C. The Fe/(Fe+Mg) ratios of amphiboles pointed out that the SJG crystallized under moderately reduced conditions, despite the common presence of magnetite in the two studied facies. Through the composition of biotites has been verified that SJG is an anorogenic pluton and its parental magma shows a trend from alkaline varieties toward subalkaline compositions, typical of A-type granites. The comparison between the SJG and the granitic suites of the Carajás Province, based on the mineral chemistry and crystallization conditions, reinforces previous works that included this pluton in the Serra dos Carajás Suite. This study proves that the scanning electron microscopy can provide reliable and satisfactory results regarding to mineral chemistry of amphiboles and biotites and to crystallization conditions.